Performance evaluation and optimization studies of border irrigation system for wheat in the Indian Punjab - Kaur, Samanpreet; Raheja, Amina; Aggarwal, Rajan (Water SA, 2019)
Surface irrigation methods are the most widely practiced worldwide for irrigation of row crops. The major problem with these methods is low irrigation efficiency, mainly due to poor design. In the Punjab, border irrigation is used to irrigate wheat crops grown over 90% of the cultivated area. The evaluation of existing border systems using a surface irrigation model showed that the irrigation conditions, comprising of inflow rate, border dimensions, and cut-off time, were diverse in tubewell and canal irrigated areas. The study also examined the feasibility of optimizing border dimensions taking into consideration the existing irrigation conditions for achieving more than 60% application efficiency as compared to the 30–40% achieved under present field conditions. In the case of a border length of 60 m, it was recommended to increase border width in the range of 10–45 m and 20–60 m for different flow rates of 10, 20 and 30 L/s in light and medium soils, respectively. For higher flow rates, a border length ranging from 120–150 m was found to be optimum. For a border length of 150 m, it was recommended to keep a border width ranging from 4–38 m and 8–65 m in light soils and medium soils, respectively, for flow rates of 10, 20, 30 and 60 L/s. Optimizing border dimensions is a practical way to achieve efficient and judicious use of water resources.